Analisis Pertumbuhan Investor Ritel Pada Masa Pandemi Dan Implikasi Pajak Penghasilan Final Atas Penjualan Saham Di Bursa - Muhammad Hammam Rafati Lubis; I Gede Komang Chahya Bayu Anta Kusuma (Politeknik Keuangan Negara STAN, 2022)
The Covid-19 pandemic has had a domino effect on the Indonesian economy and stock market. However, in the midst of a sluggish economy, there was a significant increase in the number of retail investors on the Indonesia Stock Exchange. This study aims to analyze the characteristics and level of tax compliance of retail investors who decide to invest in stocks during the pandemic, and to determine the impact of final income tax receipts on stock sales during the pandemic. The research method used is a qualitative method. The research was conducted using primary data and secondary data. Primary data used in the form of open questionnaire data to 120 retail investors. The secondary data used is data on final income tax receipts from the sale of shares from DJP, data on the volume and value of stock trading transactions from IDX, and investor demographic data from KSEI. The results showed that the majority of retail investors who decided to invest in stocks during the pandemic were under 30 years old, had a monthly income of less than IDR 4.8 million, and had a short-term investment type (trading). The level of tax compliance of retail investors who decide to invest in stocks during the pandemic has been formally good but still materially low. The Covid-19 pandemic had a positive impact on increasing final income tax receipts from the sale of shares on the stock exchange. This is due to a significant increase in the volume and value of stock trading transactions at the end of 2020 to early 2021 which shows a sense of investor optimism and is offset by an increase in the number of retail investors.